Law of torts - Lakshminath, A.; Sridhar, M. (New Delhi, 2003)
Ramaswamy Iyer s The Law of Torts is a concerted effort made to streamline the various concepts in the tort law. This is a comprehensive and detailed book critically analysing in detail the nuances of the tort concept.
Keywords: Law of Torts